A phase diagram of Ba1‐xCaxTiO3 (x = 0‐0.30) piezoceramics by Raman spectroscopy. Issue 6 (19th January 2018) - Shu, Chang; Reed, Daniel; Button, Tim W.
Abstract: Piezoelectric ceramics are widely used in sensors, actuators, and ultrasonic transducers due to their ability to achieve efficient conversion between electric and mechanical energy. There is a current drive toward lead‐free material systems capable of achieving comparable piezoelectric performance to environmentally hazardous, but commonly used, lead‐based materials such as lead zirconate titanate. This work constructs an accurate phase diagram for barium calcium titanate (Ba1‐x Cax TiO3 or BCTO). The substitution of Ca 2+ on the Ba‐site of BCTO is of much interest due to electric property improvements compared to BaTiO3 . In this work, Ba1‐x Cax TiO3 ( x = 0‐0.30) samples have been made by solid‐state methods and, following initial characterization by X‐ray diffraction (XRD), evaluation of changes in the Raman spectra has allowed accurate determination of the phase transition temperatures and the construction of a phase diagram.